Delignification and fruit juice clarification properties of alginate-chitosan-immobilized ligninolytic cocktail. (July 2017) - Bilal, Muhammad; Asgher, Muhammad; Iqbal, Hafiz M.N.; Hu, Hongbo; Zhang, Xuehong
Abstract: In the present study, an in-house extracted ligninolytic enzyme cocktail from Ganoderma lucidum IBL-05 was effectively immobilized on alginate-chitosan beads using glutaraldehyde. The firm quality stable alginate-chitosan beads developed using optimum condition of 3.0: 0.5% (w/v), alginate: chitosan ratio; 1.0% (v/v) glutaraldehyde concentration and 0.5 mg/mL of protein concentration registered the maximum immobilization yield. The functional characteristics and surface morphology of the control and ligninolytic enzyme conjugated alginate-chitosan beads were characterized using Fourier-transform infrared and scanning electron microscopy, respectively. Evidently, after enzymatic treatment, a significant reduction in turbidities up to 84.02%, 57.84%, 86.14%, and 82.13% was recorded for apple, grape, orange and pomegranate juice, respectively. The enzymes were subsequently used for the delignification of various agro-industrial materials. The immobilized consortium caused the marked reduction in lignin content of all the plant residues with a maximum delignification of 57.3% in sorghum stover after 15 h. In conclusion, the study suggests the potential of the immobilized ligninolytic enzyme, as a cost-effective industrially desirable green catalyst, for biotechnological at large and industrial in particular, especially for delignification, food, and beverage applications. Highlights: Green catalyst: a promising & eco-friendly tool to treat natural polysaccharides was developed. Alginate-chitosan immobilized ligninolytic cocktail with novel characteristics for fruit juice clarification. Apple, grape, orange, and pomegranate fruit juice clarification within a shortest time period.